Influence of Ethical Culture, Locus of Control, and Money Ethics on Ethical Perceptions of Tax Evasion - Revan Mairjal; Nabila Qotrunnada; Tjoa Han Hwa (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
This study aims to prove the ethical culture, locus of control, and money ethics on the ethical perception of tax evasion. The independent variables used in this study are ethical culture, locus of control, and money ethics, while the dependent variable is the ethical perception of tax evasion. This research was conducted at Pamulang University. The research method used is descriptive quantitative. The type of data used is primary data in a questionnaire distributed to Pamulang University Accounting Students online using a google form. Samples were collected by the accidental sampling method (convenience sampling). Respondents used for this study sample were 125 people with specific criteria to obtain 100 samples. Data processing using SPSS version 25.0 for windows by collecting data and related data is then calculated ethical culture, locus of control, and money ethics through testing using multiple linear regression analysis methods. This study indicates that partial ethical culture does not affect ethical perceptions of tax, locus of control affects the ethical perception of tax evasion, and money ethics has no effect on tax evasion. At the same time, the test results show that ethical culture, locus of control, and money ethics affect the ethical perception of tax evasion